Hurdles and limitations for design of a radial permeameter conforming to the benchmark requirements - Sousa, Pedro; Lomov, Stepan V.; Ivens, Jan (Frontiers in Materials, 2022)
Experimental permeability measurements saw a considerable increase in accuracy when recommendations and guidelines were imposed upon the realization of two international benchmarks. Such requirements aid the design stage and experimental validation of a permeameter rig however, systematic errors in the measurements still compromise the comparability of measurements obtained by different radial permeameter rigs. Owing to hurdles and limitations in the data acquisition system, validation of the mold cavity and fluid injection system, optical errors in the visual tracking of a flow front, and uncertainties in the measurement of the fluid viscosity, the measurement’s accuracy is yet lower than the required for a standardized process. In this study, the detailed study and calibration of such parameters was able to identify and minimize error sources that would otherwise result in undetected systematic deviations from the expected results. In conclusion, the verification proposed by the radial benchmark does not guarantee the accuracy of the measurement, as the error in the instruments proposed for the verification is comparable to the requirements themselves. This creates a certain uncertainty in the verification that needs to be tackled with more detailed measurement protocols to ensure not only the compliance with the measurement requirements but also to set the limits of the attainable accuracy. The rig was validated by measuring the permeability of the fabric reinforcements used in the radial benchmark exercise. Due to the scattering in the results reported in the benchmark exercise, 13 out of the 19 reported values were excluded to obtain a good estimation of the expected permeability for each volume fraction. Although the rig complied with all recommendations currently in place, the obtained permeability showed a 20% deviation in the K1 direction, while the K2 was within the expected range for the average value. The observed deviation was later found to be caused by an optical distortion, which affected the measurement of the real-world flow front dimensions. A correction for this deviation needs further systematic investigation, also a possible revision of the future standard since a correction for optical distortions is yet not included in the measurement guidelines.